Paradise Regained? Localised and Limited Nature Connexions in the UK's Covid-19 Lockdown - Dobson, Julian; Gore, Tony; Graham, Kim; Swade, Kate (Frontiers in Sustainable Cities, 2021)
Research has suggested that connections between humans and the natural world lead to increased wellbeing (Howell et al., 2011; Pritchard et al., 2019) and generate pro-environmental attitudes, which in turn benefit nature. This article asks whether users of outdoor public spaces in the UK during the Covid-19 pandemic in 2020 experienced greater connectedness with nature, consistent with the five ‘pathways to nature connectedness’ identified by Lumber et al. (2017). Semi-structured interviews were conducted with a purposive sample of 42 individuals on their use of green and public spaces during the UK’s lockdown, while a further 29 participants responded to an online survey. While the research revealed the importance of nature connectedness, only three of the five pathways were well evidenced, and these connections were frequently mediated by social activities. The article advances the study of nature connectedness by identifying challenges in applying the pathways framework and suggesting areas for further research to understand how the pathways operate in real-world conditions.